PENGARUH PEMBERDAYAAN PEGAWAI TERHADAP PENINGKATAN PELAYANAN PUBLIK DI KANTOR KECAMATAN MALALAYANG KOTA MANADO - TIGAUW, GRACIELLA; DENGO, SALMIN; MAMBO, RULLY (Sam Ratulangi University, 2021)
This study aims to determine the effect of employee empowerment on improving public services in theMalalayang District of Manado. This study uses quantitative research methods with the amount of samplestaken are all members of the population, amounting to 35 people, instruments and data collection techniquesused in this study are questionnaires and interviews. The results of a simple regression analysis test showthat employee empowerment has a significant influence on employee performance this sees the value ofcorrelation (R) of 0.731 and the coefficient of determination (Squere) 53.4% which means that the effect ofthe independent variable on the dependent variable is 53, The remaining 4% are 46.6% influenced by otherfactors.Keywords: Employee Empowerment, Public Service